Community Participation in the Citarum Harum Program: A Review of Legal Aspects - Mohammad Solekhan (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The Citarum river problem has been trying to be resolved for a long time. However, this problem is complicated to address because the community is often not involved, even though the community is one of the main components of environmental conservation. This research then looks at how community participation in the Citarum Harum program is viewed from a legal perspective. This study uses a qualitative approach. The data used in this research is secondary data that comes from different research results and studies, as well as laws that still have relevance to the contents of this research. The results of this study then found that community participation helped implement the Citarum Harum program. As viewed from the legal aspect, community participation is in line with Law No. 32 of 2009 concerning the Protection and Management of the Environment and Presidential Regulation Number 15 of 2018 concerning the Acceleration of Control of Pollution and Damage to the Citarum River Basin.